Lifestyle and high density lipoprotein cholesterol in postmenopause. (February 2014) - Di Blasio, A.; Bucci, I.; Ripari, P.; Giuliani, C.; Izzicupo, P.; Di Donato, F.; D'Angelo, E.; Napolitano, G.
Abstract Objectives Menopause is characterized by hormonal and metabolic changes. These are linked to increased risk of cardiovascular disease, for which low blood plasma levels of high density lipoprotein (HDL) cholesterol are an independent risk factor. The present study investigated variables linked with basal plasma HDL cholesterol levels and the effects of aerobic training, on their variations, in 40 postmenopausal women. Methods We assessed body composition, dietary habits and maximal aerobic capacity of participants. Characteristics of daily physical activity and plasma lipoproteins were measured. The women walked on 4 days/week, for 14 weeks, at moderate intensity, and they were grouped according to the resulting tertiles of basal plasma HDL cholesterol levels. Results Logistic regression analysis showed that waist-to-hip ratio and number of daily bouts of moderate-intensity physical activity, held for at least 10 consecutive minutes (B10m/day), are predictive variables of basal plasma HDL cholesterol levels. After the training period, the first and second tertiles increased plasma HDL cholesterol levels, while the third tertile decreased plasma HDL cholesterol levels. The tertiles showed different remodelling of spontaneous physical activity: the third tertile reduced B10m/day, while the others did not. Conclusions This study provides knowledge about the relationships of plasma HDL cholesterol levels with characteristics of physical activity. Furthermore, it shows that physical exercise engagement can result in negative compensation of spontaneous physical activity that could counteract or reduce the positive effects of the aerobic training on plasma HDL cholesterol levels.